Evaluation and analysis of noise levels in hospitals: A preliminary investigation - Che Din, Nazli (2013)
Creating a healing environment is important for hospital care and increasing attention has been paid to the ambient health care physical environment, including effects of the sensory stimuli such as sound. In this study, a preliminary investigation of the acoustic environments in the waiting areas in hospitals was conducted. The aim of this study was to clarify the actual conditions in two waiting areas in two hospitals in Kuala Lumpur, Malaysia. The investigations consist of both noise level measurements and questionnaire surveys. At first, meas-urement of noise levels were recorded over an eight hour period and converted into different levels (LAeq and LAmax). In general, noise levels for both hospitals are strongly influenced by noise produced during general activities in waiting areas. It was found that the noise level LAeq in all waiting areas measured exceeded the recommended levels. Then, respondents were interviewed in the course of a questionnaires survey dealing with nuisance occasioned by noise sources during respondent's waiting time. The survey results in both waiting areas in two hospitals also support the measurement results. This paper gives a fundamental data for the help of future refinements.